(untitled) (International Journal of Food and Nutritional Sciences, 2022)
ManjuKapur, has presented an interesting image of a woman who represents the delight and the distress of being married, in her second novel A Married Woman. ManjuKapur, in this novel the protagonist as the daughters has an educated middle -class Delhi woman and could ask for a loving and wealthy surrounding and yet inspired with a sense of dissatisfaction. She begins an extra marital affair. She describes men and women relationship consists of multiple identity quest of heroine, the protagonist Astha, who initially feels sense of separation from her married life and family. But finally leaves herself to accepting truth, by reviews her relationship with her husband as a mark of conclusion that is refreshing man and relationship which is vital one for all human being in this common world.